EVALUATION OF THE POTENTIAL ACARICIDAL OF THE HEXANIC EXTRACT OF Trichilia pallida SW. (SAPINDALES: MELIACEAE) LEAVES AND ESSENTIAL OIL OF Sesamum indicum LINN. (LAMIALES: PEDALIACEAE) SEEDS AGAINST LARVAL INSTAR OF Rhipicephalus sanguineus (LAT.) (IXODIDAE - Inácio, Cecília de Oliveira; Fernandes-Pires, Ellen de Freitas; Castro Jr., Laurindo Camilo de; D'Alessandro, Walmirton Bezerra; Leles, Renan Nunes; Fazolin, Murilo; Marques, Emerson Finco; Vieira, Paulo Cezar; Fernandes, Fernando Freitas (SaBios-Revista de Saúde e Biologia, 2019)
This paper aims at verifying the potentials of Trichilia pallida and Sesamum indicum in the prospection of botanical acaricide, to be used as a new alternative to R. sanguineus control. Hexanic extract (h.e.) of T. pallida leaves and essential oil from seeds of S. indicum were obtained in laboratory, from samples collected, respectively, in an area of Atlantic forest and in agricultural farms, in Brazil. R. sanguineus larvae were obtained from engorged females collected in naturally infested urban environs. Bioassays were carried out in quadruplicate, at 27 ± 1ºC, RH ≥ 80% and photoperiod of 12 hours. About 50 larvae, from 14 to 21 days of age, were conditioned in filter paper envelopes, impregnated with different concentrations of vegetable substances, obtained from dilution of stock solution. In each bioassay, four envelopes impregnated with each tested concentration were used. The control group used the same amount of larvae, submitted to: 1. envelopes with no treatment; 2. envelopes with distilled water and, 3. envelopes having solvents used in the preparation of vegetable solutions. For the action of h.e. leaves of T. pallida and S. indicum oil, after 24h of exposure, it was obtained, respectively, LC50 of 4,660 ppm and 107,729 ppm and LC99 of 14,217 ppm and 279,912 ppm. After 48h, it was obtained, respectively, LC50 of 1,555 ppm and 78,880 ppm and LC99 of 3,431 ppm and 221,255 ppm. There was no significant mortality rate within the control group (P < 0.05). RESUMO Este trabalho objetiva verificar os potenciais das plantas Trichilia pallida e Sesamum indicum na prospecção de acaricidas botânicos, para serem utilizados como nova alternativa para controle do ixodídeo Rhipicephalus sanguineus. O extrato hexânico (e.h.) de folhas de T. pallida e o óleo essencial de sementes de S. indicum foram obtidos em laboratório, a partir de amostras coletadas, respectivamente, em uma área de Mata Atlântica e em fazendas de cultivo no Brasil. Larvas de R. sanguineus foram obtidas a partir de fêmeas ingurgitadas, coletadas em ambientes urbanos naturalmente infestados. Os bioensaios foram realizados em quadruplicata, a 27 ± 1ºC, RH ≥ 80% e fotoperíodo de 12 horas. Cerca de 50 larvas, de 14 a 21 dias de idade, foram acondicionadas em envelopes de papel-filtro, impregnados com diferentes concentrações das substâncias vegetais, obtidas a partir da diluição de soluções-padrão. Em cada bioensaio, foram utilizados quatro envelopes impregnados com cada concentração testada. O grupo controle usou a mesma quantidade de larvas, submetidas a: 1. Envelopes sem nenhum tratamento; 2. Envelopes tratados com água destilada e, 3. Envelopes com solventes utilizados na preparação de soluções vegetais. Pela ação do h.e. de folhas de T. pallida e do óleo de S. indicum, após 24 horas de exposição, obtiveram-se, respectivamente, CL50 de 4.660 ppm e 107.729 ppm e CL99 de 14.217 ppm e 279.912 ppm. Após 480 h, obtiveram-se, respectivamente, CL50 de 1.555 ppm e 78.880 ppm e CL99 de 3.431 ppm e 221.255 ppm. Mortalidade larval significativa não foi observada no grupo controle (P < 0,05).